Pharmacological activities and phytochemical constituents of Phyllanthus reticulates Poir. – A review - Sathasivampili, S.V.; Jeyaseelan, E.C. (Faculty of Science, University of Jaffna, 2020)
Phyllanthus reticulatus Poir. (Phyllanthaceae) is a shrub distributed in Australia, Asia, and Africa. Various parts of this plant species are employed to cure a variety of illnesses in ethnomedicines such as urine infection, malaria, headache, dysmenorrhea, abscess, anemia, asthma, diarrhea, smallpox, syphilis, inflammation, rheumatism, sores, and envenomation. So far, there is no systematic comprehensive review has been published to analyze, summarize, and document the scientific finding of phytochemistry and pharmacological activities of this plant species. Hence, this work aims to present a comprehensive review to offer a base and encourage to carry out further phytochemical and pharmacological researches of P. reticulatus. The Web of Science was utilized to identify the appropriate published articles from 1900 to September 2020. Compounds including astragalin, corilagin, isoquercitrin, taraxerone, pinoresinol, friedelin, reticulate side A, and sitosterol been identified in this plant species. So far, only in vitro and in vivo scientific evidence are available for the pharmacological activities of various parts of P. reticulatus and more investigations involved in vitro bioassays. Researches show that P. reticulatus contains analgesic, antibacterial, antidiabetic, antifungal, anti-human immunodeficiency virus-1, antihypercholesterolemic, anti-inflammatory, antioxidant, antiplasmodial, and hepatoprotective activities. Further, none of the pharmacologically active compound has been recognized in this plant species. Hence, additional pharmacological activities and phytochemical analysis studies should be performed to deliver more scientific evidence for ethnomedicinal uses of this plant species. This work summarized the available phytochemical and pharmacological activities findings of P. reticulatus and also delivers a foundation for additional phytochemical and pharmacological activities investigations of P. reticulatus.
Keywords: Phyllanthus reticulatus; Phyllanthaceae; Sri Lanka; Siddha Medicine; Ayurveda